Association of TNFα and IL1β genotypes with the risk of Staphylococcus aureus causing recurrent tonsillitis in a sample of Iraqi patients: Association of TNFα and IL1β genotypes with recurrent tonsillitis - Jasim Mohammed, Bushra; Howraa Fadhil (Iraqi Journal of Cancer and Medical Genetics, 2024)
Background and aim: Tonsillitis is an inflammation of the tonsils, usually caused by an infection by viruses or bacteria; recurrent tonsillitis occurs when tonsillitis occurs several times a year. The current study aimed to investigate the association of TNFα and IL1β genotypes with the increased risk of recurrent Staphylococcus aureus tonsillitis in a sample of Iraqi patients. Methods: A total of 50 blood samples were collected from patients with recurrent tonsillitis of S. auerus from three hospitals in Najaf city, and 50 samples were collected from apparently healthy volunteers with a free medical history of recurrent tonsillitis as control group. Genomic DNA was extracted from peripheral blood and genotyped for TNF-α 308G/A and IL1β C/T SNP using Nested tetra-primer amplification refractory mutation system PCR (T-ARMS-PCR). Results: The results of the distribution IL β –rs1143627 C/T alleles in S. aureus tonsillitis patients showed CC wild type genotype was in 11 patients (22%), CT genotype was in 30 patients (60%) and the TT genotype was in 9 patients (18 %) also C allele frequency was (0.42), whilst T allele frequency was (0.58) with Odds Ratio (1.507) at significant difference (P≤ 0.01), while prevalent of TNF-α –rs1800629 G/A alleles genotype in S. aureus tonsillitis patients revealed that GG wild type genotype was 37 patients (74%), GA genotype was 13 patients (26%) and AA genotype was 0(0%) also, G allele frequency was (0.87) and A allele frequency was (0.13) with Odds Ratio (1.507) at no significant differences in both the patient and control.